Mineral levels of Bali cattle (Bos javanicus) from different types of land in Bali, Nusa Penida, and Sumbawa Islands (Indonesia) - I Nengah Kerta Besung; NI LUH WATINIASIH; GUSTI NGURAH KADE MAHARDIKA; KADEK KARANG AGUSTINA; NI KETUT SUWITI (Society for Indonesian Biodiversity, 2019)
Abstract. Besung INK, Watiniasih NL, Mahardika GNK, Agustina KK, Suwiti NK. 2019. Mineral levels of Bali cattle (Bos javanicus) from four different types of land in different rearing areas in Bali, Nusa Penida, and Sumbawa Islands (Indonesia). Biodiversitas 20: 2931-2936. This study aims to prove that the mineral level of Bali cattle in serum is dependent on the origin and raising habitat. Serum samples were collected from three islands in Indonesia, i.e. Bali, Nusa Penida, and Sumbawa. Samples from Bali were further classified into four different areas (i.e. agroforestry, perennial plantation, horticultural plantation, and rice field). Blood samples were collected in the jugular vein without anticoagulant. The contents of macrominerals (Ca, Mg, Na, K, P) and microminerals (Fe, Cu, Zn, Co, Mn) were measured using the flame method in atomic absorption spectrophotometer. The results showed that the level of phosphor (P) macromineral and all microminerals under study were influenced by the origin of cattle. The macrominerals are statistically varied in different cattle raising environments. The same is also valid for all microminerals, with an exception of Fe. All mineral levels under study were statistically equal in male and female Bali cattle. Phosphor macromineral and all microminerals levels were origin and environment-dependent. Supplementation of deficient minerals in a certain area and land type is recommended to improve the performance of Bali cattle.